The sacred and the impure in Judaism: law, food, and identity - Topel, Marta F. (Oxford scholarship online, 2024)
'The Sacred and the Impure in Judaism' examines the radicalization of certain Orthodox Jewish groups through the lens of kashrut, or Jewish dietary laws.